2014
DOI: 10.1108/nlw-03-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Keeping up with the law: investigating lawyers’ monitoring behaviour

Abstract: Abstract:Purpose:We wanted to provide an enriched understanding of how lawyers keep up-to-date with legal developments. Maintaining awareness of developments in an area (known as 'monitoring') is an important aspect of professional's information work. This is particularly true for lawyers, who are expected to keep up-to-date with legal developments on an on-going basis.Design/methodology/approach:We conducted semi-structured interviews with a group of lawyers who authored and published current awareness conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The legal profession involves a great extent of information and knowledge (Ellis et al, 2014;Komlodi, 2002Komlodi, , 2004. In order for lawyers to fulfill their duty, they need "the cases, the statutes, and the regulations which govern a particular problem or area related to a particular factual situation" (Cohen, 1969, p. 185).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The legal profession involves a great extent of information and knowledge (Ellis et al, 2014;Komlodi, 2002Komlodi, , 2004. In order for lawyers to fulfill their duty, they need "the cases, the statutes, and the regulations which govern a particular problem or area related to a particular factual situation" (Cohen, 1969, p. 185).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lawyers' information needs are subjected to time constrains and to the complexity of their legal cases (Chancellor, 2010;Makri et al, 2007). Because legal literature evolves quickly, together with the recurring amendments to statues, rules and regulations and with the constant juristic progress in courts' rulings (Rai, 2013), lawyers must keep informed in order to provide their clients with the up-to-date and correct understanding of the law (Ellis et al, 2014;Komlodi, 2002;Komlodi et al, 2007). But, although access to court rulings makes it possible for lawyers to study and analyze different legal situations, 112 AJIM 68,1 identify legal shifts and use these intelligently in their legal work such as in constructing case-based legal arguments (Halperin-Kaddari and Blutner, 2013;Ellis et al, 2014), finding the key relevant court rulings directing the legal issues under inquiry is in many cases actually a difficult task (Best, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Echoing past research this study found that information assimilation fundamental is one of the legal pivots in the practice of law in Israel that expounds the mere professional gathering of information encompassing different practices (Verberne et al, 2019). One important practice in this set is being knowledgeable in the current law in relation to the issues put before them and its valid up-to-date interpretation, based on the notion that access to legal information is a critical component for effective justice (Al-Daihani and Oppenheim, 2008) and lawyering (Cohen and Olson, 2016;Ellis et al, 2014;Flood, 2019;Jamshed, 2020;Otike, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A complementary aspect of this socially inclined information practice of Israeli lawyers is keeping in touch with their clients on their issues and providing them with personal support in needed instances. These two are either semi-legal assistive in favor of the client as in cases of alternative non-adversary conflict-resolution processes (Bogoch et al, 2002), or altruistic in favor of colleagues (Ellis et al, 2014;Jamshed, 2020;Wilkinson, 2001). This finding is novel and apparently opposed to lawyers' information non-sharing culture, stressed by Susskind (2003), Choo et al (2008) and Evans and Price (2018), due to their subjective risk of losing the competitive edge of the shared information.…”
Section: Discussionmentioning
confidence: 99%
“…Further, he stressed that the curriculum of law courses ought to have legal information literacy components that students can understand how to get the desired information. Bhardwaj and Madhusudan 23 carried out a study on academic lawyers and found that (97.77 %) respondents are aware of open access resources; however, only (71 %) frequently use the resources and (15.55 %) rarely use these resources. The study also found that the main purposes of using these resources are case law searching (nearly 39 %), followed by project and assignments (26.66 %), and study and update (24.44 %).…”
Section: Literature Reviewmentioning
confidence: 99%